Effects of short term bioturbation by common voles on biogeochemical soil variables - Wilske, Burkhard; Eccard, Jana (Prof. Dr.); Zistl-Schlingmann, Marcus; Hohmann, Maximilian; Methler, Annabel; Herde, Antje (Dr.); Liesenjohann, Thilo (Dr.); Dannenmann, Michael; Butterbach-Bahl, Klaus; Breuer, Lutz (2019)
Bioturbation contributes to soil formation and ecosystem functioning. With respect to the active transport of matter by voles, bioturbation may be considered as a very dynamic process among those shaping soil formation and biogeochemistry. The present study aimed at characterizing and quantifying the effects of bioturbation by voles on soil water relations and carbon and nitrogen stocks. Bioturbation effects were examined based on a field set up in a luvic arenosol comprising of eight 50 x 50 m enclosures with greatly different numbers of common vole (Microtus arvalis L., ca. 35-150 individuals ha(-1) mth(-1)). Eleven key soil variables were analyzed: bulk density, infiltration rate, saturated hydraulic conductivity, water holding capacity, contents of soil organic carbon (SOC) and total nitrogen (N), CO2 emission potential, C/N ratio, the stable isotopic signatures of C-13 and N-15, and pH. The highest vole densities were hypothesized to cause significant changes in some variables within 21 months. Results showed that land history had still a major influence, as eight key variables displayed an additional or sole influence of topography. However, the delta N-15 at depths of 10-20 and 20-30 cm decreased and increased with increasing vole numbers, respectively. Also the CO2 emission potential from soil collected at a depth of 15-30 cm decreased and the C/N ratio at 5-10 cm depth narrowed with increasing vole numbers. These variables indicated the first influence of voles on the respective mineralization processes in some soil layers. Tendencies of vole activity homogenizing SOC and N contents across layers were not significant. The results of the other seven key variables did not confirm significant effects of voles. Thus overall, we found mainly a first response of variables that are indicative for changes in biogeochemical dynamics but not yet of those representing changes in pools.